1981
DOI: 10.3758/bf03202355
|View full text |Cite
|
Sign up to set email alerts
|

Intralanguage vs. interlanguage Stroop effects in two types of writing systems

Abstract: The relation between word processing strategy and the orthographic structure of a written language was explored in the present study. Three experiments were conducted using ChineseEnglish, Spanish-English, and Japanese-English bilinguals, respectively. Each subject was asked to perform a modified Stroop color-naming task in which the stimulus and the response language were either the same or different. The magnitude of the Stroop effect was greater in the intralanguage condition than in the interlanguage condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…Chen and Ho (1986) suggested that extreme differences between languages make it easier to resist competing stimuli in the second language, reducing the inter-lingual Stroop interference effect. This is in line with the findings of Fang, Tzeng, and Alva (1981) who analyzed the difference in Stroop interference in Chinese-English, Japanese-English and Spanish-English bilinguals and showed that as the similarity between the two languages decreased, the difference between within-and between-language interference increased. On the other hand, Costa, Santesteban, and Ivanova (2006) reported that language similarity did not affect the way bilinguals control their speech.…”
supporting
confidence: 77%
“…Chen and Ho (1986) suggested that extreme differences between languages make it easier to resist competing stimuli in the second language, reducing the inter-lingual Stroop interference effect. This is in line with the findings of Fang, Tzeng, and Alva (1981) who analyzed the difference in Stroop interference in Chinese-English, Japanese-English and Spanish-English bilinguals and showed that as the similarity between the two languages decreased, the difference between within-and between-language interference increased. On the other hand, Costa, Santesteban, and Ivanova (2006) reported that language similarity did not affect the way bilinguals control their speech.…”
supporting
confidence: 77%
“…In the cross-language version of the traditional color-word interference task, ink colors are to be named in a language different from the one in which the incongruent color words are printed. For bilinguals who are highly proficient in both of their languages, cross-language interference is consistently observed (relative to naming colors of neutral stimuli such as color patches or rows of Xs), though the interference is reduced relative to the degree of within-language interference (Abunuwara, 1992;Chen & Ho, 1986;Dalrymple-Alford, 1968;Dyer, 1971;Fang, Tzeng, & Alva, 1981;Kiyak, 1982;Lee, Wee, Tzeng, & Hung, 1992;Preston & Lambert, 1969;Smith & Kirsner, 1982). As can be seen from Table 10, the between-language interference effect relative to neutral control is on average 74% the magnitude of the withinlanguage interference effect (consistent with the average obtained by MacLeod, 1991).…”
Section: Interference Between Languagesmentioning
confidence: 99%
“…Shortly after Dyer's study, Hamers (1973;Hamers & Lambert, 1972) used her auditory Stroop analog with French-English bilinguals and reached the same conclusion: The differentlanguage condition produced about 76% of the interference seen in the same-language condition. This pattern recurs for Spanish-English bilinguals in the picture-word task (Ehri & Ryan, 1980), French-English bilinguals in the flanker-word task (Guttentag et al, 1984), and diverse languages in the color-word task (e.g., Chinese-English and Japanese-English; Fang, Tzeng, & Alva, 1981;Turkish-English: Kiyak, 1982). Fang et al (1981) also confirmed that the ratio of between-language to withinlanguage interference declines as language similarity decreases.…”
Section: Language Differences: the Case Of The Bilingualmentioning
confidence: 99%
“…This pattern recurs for Spanish-English bilinguals in the picture-word task (Ehri & Ryan, 1980), French-English bilinguals in the flanker-word task (Guttentag et al, 1984), and diverse languages in the color-word task (e.g., Chinese-English and Japanese-English; Fang, Tzeng, & Alva, 1981;Turkish-English: Kiyak, 1982). Fang et al (1981) also confirmed that the ratio of between-language to withinlanguage interference declines as language similarity decreases.…”
Section: Language Differences: the Case Of The Bilingualmentioning
confidence: 99%